A Guide to Scale Insect Identification - Stephen H. Futch; C.W. McCoy; C.C. Childers (EDIS)
Control of scale insects in Florida citrus utilizes native and introduced exotic natural enemies, including predators, parasites, and pathogens. Under most conditions, predators and parasites suppress scale pest populations to a level where chemical intervention is unnecessary. In situations where natural enemies do not provide the necessary control, integrated pest management (IPM) is used since it minimizes negative effects on natural enemies. Increases in scale insect populations involve multiple factors including: a) disruption of biological control by weather; b) infestation of areas by scale insects where natural enemies do not exist; and c) disruption of natural enemies by the repeated use of non-selective pesticides.